Cost Impact of Intrathecal Polyanalgesia. Issue 10 (24th July 2013) - Kumar, Krishna; Rizvi, Syed; Bishop, Sharon; Tang, Wei
Abstract Objective To assess the cost impact of dose escalation with intrathecal drug therapy and polyanalgesic admixtures and determine if increased cost is justified by improved pain control. Methods A retrospective analysis of 110 patients, 80 patients with chronic non‐cancer pain (Group A) and 30 with spasticity (Group B). Mean follow‐up period was 73 months (Group A) and 112 months (Group B). Parameters assessed were: demographics, drug usage, drug costs, and pain/spasticity control. Two models were developed: 1) price model—estimated drug price per refill; 2) cost model—predicts costs/day by therapy types and four common pathologies over 5 years. Results All patients started on monotherapy with 63 continuing (Group A: 39; Group B: 24), with 47 (Group A: 41; Group B: 6) requiring dual‐drug therapy of which 11 (Group A: 10; Group B: 1) progressed to triple‐drug admixtures. After starting polyanalgesic regimes, patients were able to recapture lost pain control. Cost escalation in Group A at 5 years, as demonstrated by cost modeling, was 191%, 107%, and 89% for mono‐, dual‐, or triple‐drug therapy, respectively. For Group B, most patients stayed in monotherapy and the 5‐year increase was 104%. The difference in cost between monotherapy and dual therapy for Group A was $1.97/day (baseline) to $3.28/day (5th year) and between dual and triple therapy from $2.55/day (baseline) to $4.30/day (5th year). Conclusions Polyanalgesia, while more costly, is justified based on its effectiveness in restoring pain control. Superior results are achieved when polyanalgesia is initiated early. Cost modeling enabled price prediction for the purposes of developing program budgets.